2017
DOI: 10.1186/s12920-017-0304-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of innate immunity triggered by different subtypes of influenza a viruses in human and avian hosts

Abstract: BackgroundInnate immunity provides first line of defense against viral infections. The interactions between hosts and influenza A virus and the response of host innate immunity to viral infection are critical determinants for the pathogenicity or virulence of influenza A viruses. This study was designed to investigate global changes of gene expression and detailed responses of innate immune systems in human and avian hosts during the course of infection with various subtypes of influenza A viruses, using colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 60 publications
2
28
0
1
Order By: Relevance
“…As such, the possibility for a potential role for this chemokine in respiratory infections is warranted. Indeed, CXCL17 along with other chemokines such as CXCL1, 8, 10, 11 and 16 has been found to be highly expressed in human bronchial epithelial, human tracheobronchial epithelial and A549 cells infected with influenza A/H3N2 virus but reduced in these cells infected with A/H5N1 and A/H7N9 strains [87]. Avian influenza A/H5N1 and A/H7N9 strains are more virulent due to acquired genetic properties contributing to a faster replication rate and rate of infection compared to seasonal influenza A/ H1N1 and A/H3N2 strains [88,89].…”
Section: Cxcl17 In Respiratory Viral Infectionsmentioning
confidence: 99%
“…As such, the possibility for a potential role for this chemokine in respiratory infections is warranted. Indeed, CXCL17 along with other chemokines such as CXCL1, 8, 10, 11 and 16 has been found to be highly expressed in human bronchial epithelial, human tracheobronchial epithelial and A549 cells infected with influenza A/H3N2 virus but reduced in these cells infected with A/H5N1 and A/H7N9 strains [87]. Avian influenza A/H5N1 and A/H7N9 strains are more virulent due to acquired genetic properties contributing to a faster replication rate and rate of infection compared to seasonal influenza A/ H1N1 and A/H3N2 strains [88,89].…”
Section: Cxcl17 In Respiratory Viral Infectionsmentioning
confidence: 99%
“…Indeed, previous research showed that the infection of human bronchial epithelial cells, human tracheobronchial epithelial cells, and human alveolar A549 cells with seasonal in uenza A(H3N2) virus, promotes robust upregulation of CXCL17. However, the infection with more virulent A(H5N1) and A(H7N9) in uenza virus subtypes induces minor changes in the expression of CXCL17 [18]. Similarly, in a yet unpublished experiment available from the In uenza Research Database (IRD), the infection of 2B-4cells/sorted Calu-3 cells with a wild type strain of the 2002-2003 SARS-CoV (icSARS CoV) did not stimulate strong expression of CXCL17 [19].…”
Section: Discussionmentioning
confidence: 99%
“…The role of IFITMs against AI viruses in avian species has not been clearly defined, though a study by Smith and colleagues has shown that chicken IFITM3 (which is “human IFITM1-like”) similarly restricts H5 and H7 expressing viruses ( 143 ). However, when chickens were infected with H5N1, expression of IFITM molecules was not highly upregulated compared to other human-infecting seasonal strains such as H1N1, with IFITMs showing the weakest inhibiting effect against H7N9 ( 144 ). Hence, IFITM expression in chickens appears to be limited and does not vary greatly whether the virus is of low or high pathogenicity.…”
Section: Host Susceptibility Factorsmentioning
confidence: 99%